Advanced patch-clamp analysis for neuroscientists - Acker, Corey D.; Almog, Mara 1977-; Antic, Srdjan D.; Feldmeyer, Dirk; Gasparini, Sonia; Korngreen, Alon 1967- (New York : Humana Press, 2016)
This volume presents current adaptations of the patch-clamp technique to neuroscience. Chapters focus on in-vivo recordings, voltage-gated channel recording and analysis, dendritic and axonal recordings, synaptic current recording and analysis, advanced fluorescent techniques, optogenetics and voltage-sensitive dye imaging, and finally channel and neuronal modeling. Written for the popular Neuromethods series, chapters include the kind of detail and key implementation advice that ensures successful results in the laboratory.
La función de los autores fue determinada por el catalogador
Tambien disponible en formato EPUB
Keywords: TÉCNICAS DE FIJACIÓN DE MEMBRANA (ELECTROFISIOLOGÍA) -- MANUALES DE LABORATORIO; NEUROCIENCIAS; ELECTROFISIOLOGÍA; CANALES IÓNICOS; NEURONAS; TÉCNICAS DE FIJACIÓN DE MEMBRANA (ELECTROFISIOLOGÍA)